Cine colombiano en el siglo XXI. Balance de las coproducciones colombianas con Europa. Issue 2 (4th May 2018) - Rocha, Carolina
ABSTRACT: This article traces the development of Colombian cinema in the twenty-first century, paying particular attention to the co-productions between Colombia and European countries in the last sixteen years. The analysis of these co-productions shows the importance of foreign funds in the production of Colombian films, particularly in the wake of the approval of Law 814 that aimed to foster Colombian film production. The article focuses on four different types of Colombian-European co-productions: those made with support from Ibermedia, France, Spain and other European countries, and the Colombian producers and directors who were instrumental in their making. Colombian-European co-productions contributed in strengthening Colombian cinema, particularly supporting the uninterrupted shooting of films. Without sacrificing authenticity in plots nor reference to national topics, Colombian-European co-productions have enjoyed access to larger audiences.